Heterogeneity in Anxiety Disorder and Autism Spectrum Disorder: Difference and Overlap - Ziadatul Hikmiah (The Center for Disability Studies and Services Brawijaya University, 2019)
Research on the expression and prevalence of co-occurring anxiety disorders and autism spectrum disorders (ASD) has produced variable results. In part this is due to heterogeneity in the characteristics of the samples, methodology, and the underlying cause of anxiety disorders and ASD across studies. This review will focus on the aspects related to the manifestation of anxiety disorders in children with autism spectrum disorder (ASD), in order to establish the amount of comorbidity or heterogeneity both within and between these disorders. This review will also elaborate on the findings from related studies with reference to the underlying causes of both disorders. A number of typical anxiety symptoms play a significant role characterising autism, creating overlap and heterogeneity in the disorders. Therefore, further research on the measurement of anxiety symptoms in children and adolescents with ASD in addition to the interaction of anxiety and social disability in this population is required, so appropriate treatment and intervention can be established to address each specific characteristic of these disorders.